The new slave trade in Libya: evaluating the modern humanitarian crisis (2015–2024) - Festus Jusu Lahai (Frontiers in Political Science, 2025)
The resurgence of modern slavery in Libya, marked by the commodification of migrants in detention centers and open-air markets, reflects systemic global inequalities and geopolitical complicity. Using Marxist analysis and a Libya case study, this qualitative study draws on NGO and IGO reports (IOM, MSF, HRW) to reveal how neoliberal capitalism, imperialist interventions, and racial hierarchies sustain trafficking. NATO’s 2011 overthrow of Gaddafi dismantled Libya’s welfare state, enabling militias to privatize oil wealth (85% of revenues) and exploit migration routes. EU policy initiatives between 2017 and 2023 allocated €455 million in funding to Libyan militias, resulting in the interception of 38,000 migrants on the Mediterranean by these militias groups. This cooperation coincided with human rights violations, including torture and forced labor inflicted on 73% of intercepted individuals, alongside a concurrent rise in Mediterranean crossing fatality rates to 1 in 23 during this period. The UN’s reliance on militia cooperation and the AU’s inadequate response perpetuate impunity. Marxist critique frames sub- Saharan Africans, displaced by IMF austerity and climate crises, as capitalism’s “reserve army,” reduced to disposable labor. Racial capitalism exacerbates this, with Black migrants facing disproportionate enslavement. Libya’s fragmentation into rival factions (GNA, HoR/LNA, militias) and corporate complicity, e.g., ENI’s oil extraction via traffickers highlight international culpability. The study recommends redirecting EU funds to Sahelian climate resilience, prosecution of traffickers and corporations via ICC/Magnitsky sanctions, empowerment of local governance, expansion of legal migration pathways, and enforcement of binding corporate accountability. Libya’s crisis epitomizes global capitalism’s moral bankruptcy, demanding structural equity to prioritize dignity over profit.